Pengaruh Pelayanan, Lokasi dan Promosi Terhadap Kurangnya Minat Mahasiswa FKIP Universitas Muslim Nusantara (UMN) Al Washliyah Menabung di Bank Syariah - Cita Ayni Putri Silalahi; Dalmi Iskandar Sultani (ARBITRASE: Journal of Economics and Accounting, 2020)
Sharia banking is a financial institution that puts forward sharia principles that can provide its own convenience for its customers. This research was conducted to see the effect of service, location and promotion on the lack of interest of Al Washliyah Muslim Nusantara University (UMN) FKIP students to save in Islamic banks. The sample technique in this study is the saturated / census sampling method based on the availability of data according to the research variables, amounting to 45 people. The analysis technique in this research is multiple linear regression using the SPSS version 21 program. Hypothesis testing shows that service, location and promotion variables have an effect on the lack of interest among FKIP students at the Muslim Nusantara University (UMN) Al Washliyah in saving at Islamic Bank.